Fulfilling Educational Competencies through Global Pharmacy Experiences - Lindsey M. Childs-Kean; Carol Motycka; Sven A. Normann; Randell Doty (MDPI AG, 2019)
Many Colleges of Pharmacy in the United States offer international education and practice experiences to their students. Multiple publications have described these offerings and related them back to the CAPE 2013 Outcomes. This article describes the multiple international programs offered by one College of Pharmacy, including international Advanced Pharmacy Practice Experiences, Short Study Abroad Programs, and International Health Outreach Trips. The article also details the relevant competencies associated with these international experiences.